APLIKASI PENJUALAN OLI MOTOR BERBASIS WEB PADA TOKO EUREKA PARTS - Eric Ang; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Eureka Parts is a store that sells various types of motor oil. Eureka Parts stores serve customers online where products are sold in the marketplace. Often customers ask about products first before placing an order, due to the lack of descriptions available in the marketplace, there are also obstacles where sales reports are still recorded manually or still using Microsoft Excel, therefore a design is made to make it easier for admins to manage sales. The methodology used to design this application is to use the SDLC waterfall method. Web-based sales applications are made using the Javascript language, and the Bootstrap framework using MySQL as a database. The result of this research is a web-based sales application and inventory system that facilitates the online transaction process and can also make it easier for admins to view sales reports.